Dukungan Sosial dan Religiusitas dengan Psychological Well-Being pada Warga Binaan Perempuan di Lembaga Pemasyarakatan - Nathania Diani Alidrus; Isna Asyri Syahrina; Rina Mariana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
Correctional inmates need a lot from various parties. Social support and regiusitas are also very important to be improved for inmates. This study aims to determine social and religious support with psychological well-being in inmates. The measuring instrument used in this research is the social support scale, religiosity scale, and psychological welfare scale. The sampling technique in this study used a purposive sampling technique. The sample in this study were 130 correctional inmates at the Pekanbaru Women's Correctional Institution. The validity test in this study used the Pearson Product Moment technique and the reliability used the Cronbach Alpha technique. The results of the validity coefficient on the social support scale move from rix = 0.472 to rix = 0.833, the reliability coefficient = 0.962. In religiosity, the results of the validity coefficient move from rix = 0.329 to rix = 0.844 with a reliability coefficient of = 0.953. And on the psychological welfare scale, the results of the validity coefficient move from rix = 0.312 to rix = 0.855 with a reliability coefficient of = 0.949. Based on data analysis, the correlation value between social support and psychological well-being is 0.427 with a significance level of p = 0.000 (p <0.01). The value between religiosity and psychological well-being is 0.517, with a significance level of p = 0.000 (p <0.01). Furthermore, the correlation value between social support and religiosity with psychological well-being is 0.590 with a probability value (sig. F change) = 0.0000, because the value of sig. Changes in F < 0.05, then the hypothesis can be accepted. This shows that there is a significant relationship between social and religious support with psychological well-being.